2006
DOI: 10.1111/j.1537-2995.2006.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐blood leukoreduction filters are a source for cryopreserved cells for phenotypic and functional investigations on peripheral blood lymphocytes

Abstract: Leukoreduction filters represent a valuable source of PBMNCs. These cells could be easily recovered to prepare frozen cell banks useful in basic phenotypic and functional analyses involving the main subsets of B cells and the global T-cell population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
3
28
0
1
Order By: Relevance
“…Despite the limited number of severe cases, given the relevance of these B-cell differentiation markers we determined the frequencies of CD19-, CD27-, CD38-, and CD138-positive cells within the PBMCs of 10 SLE patient samples by flow cytometry ( Table 2). The frequencies of CD19 + cells and CD27 + B cells, ranging respectively from 2-15% and 15-48%, were not significantly different from the values obtained with HC cells and similar to those previously reported for healthy individuals (Néron et al 2006). In contrast, the frequency of CD138 + cells, ranging from 1.4-10%, was well above normal ranges (p<0.002) compared with HC (0.5±0.4%), which were close to the expected normal frequency of 0.5% (Harada et al 1996).…”
Section: Cd138 + Cells Are Present At High Frequencies In Mononuclearsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite the limited number of severe cases, given the relevance of these B-cell differentiation markers we determined the frequencies of CD19-, CD27-, CD38-, and CD138-positive cells within the PBMCs of 10 SLE patient samples by flow cytometry ( Table 2). The frequencies of CD19 + cells and CD27 + B cells, ranging respectively from 2-15% and 15-48%, were not significantly different from the values obtained with HC cells and similar to those previously reported for healthy individuals (Néron et al 2006). In contrast, the frequency of CD138 + cells, ranging from 1.4-10%, was well above normal ranges (p<0.002) compared with HC (0.5±0.4%), which were close to the expected normal frequency of 0.5% (Harada et al 1996).…”
Section: Cd138 + Cells Are Present At High Frequencies In Mononuclearsupporting
confidence: 90%
“…A maximum of 14 tubes from each patient were collected, pooled, and diluted in one volume of 10 mM phosphate-buffered saline, pH 7.4. Leukocytes from healthy individuals were recovered from leukoreduction systems, as described previously (Néron et al 2006;Néron et al 2007), after informed consent and following approval by the Research Ethics Committee of Héma-Québec. Peripheral blood mononuclear cells (PBMCs) were prepared from patients and controls by density centrifugation over Ficoll-Paque (GE Healthcare Bio--Sciences Inc., Baie d'Urfé, QC, Canada) (Fecteau and Néron 2003) and stored frozen until B-cell purification.…”
Section: Blood Sample Collection From Sle Patients and Healthy Indivimentioning
confidence: 99%
“…They observed that the percentage of T cells, B cells, monocytes and dendritic cells was largely similar between PBMCs isolated from LRS cones or buffy coats, but that PBMCs from LRS cones contain more granulocytes [35, 7]. Dendritic cells isolated from LRS cones were functional and capable of activating T cell responses [3, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic cells isolated from LRS cones were functional and capable of activating T cell responses [3, 6]. B cells isolated from LRS cones have similar expression of surface markers and ability to be activated through CD40 compared to B cells isolated from buffy coats [5]. Less is known about the functionality of T cells isolated from LRS cones compared to buffy coats.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos já mostraram que a frequência leucocitária presente nos filtros de leucorredução é similar aquela encontrada no sangue (51,62,66,67), e que a frequência de células mononucleares presentes da CLR é semelhante à frequência nos filtros (45 …”
Section: Discussionunclassified